1991
DOI: 10.1111/j.1600-051x.1991.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro investigation on the loss of root substance in scaling with various instruments

Abstract: There are differing opinions as to the extent to which root cementum has to be removed during root surface instrumentation over and above that of the debridement of plaque and calculus. Similarly, the amount of tooth material removed by individual instruments is also unclear, but a trend towards less damaging methods of root surface debridement has evolved in recent years. The purpose of this in vitro study was to determine the amounts of root substance removed by 4 different methods of instrumentation, hand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 18 publications
11
106
0
1
Order By: Relevance
“…However, the cementum formation exists as a superficial layer on the root and is easily peeled off by intensive root planing during the treatment of periodontal diseases or by toothbrushing 27) . The vulnerability of the cementum layer causes the underlying dentin to be prone to exposure, hence increasing the risk of dentin hypersensitivity and root dentin caries formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cementum formation exists as a superficial layer on the root and is easily peeled off by intensive root planing during the treatment of periodontal diseases or by toothbrushing 27) . The vulnerability of the cementum layer causes the underlying dentin to be prone to exposure, hence increasing the risk of dentin hypersensitivity and root dentin caries formation.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were divided into four groups (Root Burnisher, Perio Planing Bur, Tooth Planing Bur, and Gracey Scaler group), each containing 20 specimens. Scaling and root planing were performed with water cooling at 0.98 N (100-gf) pressure for the Root Burnisher and Perio Planing Bur groups, 0.49 N (50-gf) pressure for the Tooth Planing Bur group and 4.90 N (500-gf) pressure for the Gracey Scaler group with the samples mounted on a force gauge (DPX-5T, Imada, Tokyo, Japan) (20,21). Rotation speed was 20,000 rpm with the use of the Root Burnisher or Perio Planing Bur, and 300,000 rpm with the use of the Tooth Planing Bur (16).…”
Section: Preparation Of Specimensmentioning
confidence: 99%
“…This result is in accordance with the study of Flemmig and co-workers [13,14] who found that the applied lateral force had the greatest effect on the defect volume followed by the chosen power setting and the tip angulation. The study of Ritz et al [21] also found a more pronounced tooth substance loss with increasing instrumentation forces in the range of 100 -400 p was found. The latter study suggested a force of 100 p to be used for ultrasonic instruments.…”
Section: Discussionmentioning
confidence: 82%